Effectiveness of cervical pessary compared to cervical cerclage with or without vaginal progesterone for the prevention of preterm birth in women with twin pregnancies and a short cervix: study protocol for a two-by-two factorial randomised clinical trial - Dang, Vinh Q (BMJ Open, 2020)
INTRODUCTION: Women with twin pregnancies and a short cervix are at increased risk for preterm birth (PTB). Given the burden of prematurity and its attendant risks, the quest for effective interventions in twins has been an area of considerable research. Studies investigating the effectiveness of cervical cerclage, cervical pessary and vaginal progesterone in preventing PTB have yielded conflicting results. The aim of this study is to compare the effectiveness of cervical pessary and cervical cerclage with or without vaginal progesterone to prevent PTB in women with twin pregnancies and a cervical length (CL) ≤ 28 mm. METHODS AND ANALYSIS: This multicentre, randomised clinical trial will be conducted at My Duc Hospital and My Duc Phu Nhuan Hospital, Vietnam. Asymptomatic women with twin pregnancies and a CL ≤28 mm, measured at 16–22 weeks’ gestation, will be randomised in a 1:1:1:1 ratio to receive a cerclage, pessary, cerclage plus progesterone or pessary plus progesterone. Primary outcome will be PTB <34 weeks. Secondary outcomes will be maternal and neonatal complications. We preplanned a subgroup analysis according to CL from all women after randomisation and divided into four quartiles. Analysis will be conducted on an intention-to-treat basis. The rate of PTB <34 weeks’ gestation in women with twin pregnancies and a cervix ≤28 mm and treated with pessary in our previous study at My Duc Hospital was 24.2%. A sample size of 340 women will be required to show or refute that cervical cerclage decreases the rate of PTB <34 weeks by 50% compared with pessary (from 24.2% to 12.1%, α level 0.05, power 80%, 5% lost to follow-up and protocol deviation). This study is not to be powered to assess interactions between interventions. ETHICS AND DISSEMINATION: Ethical approval was obtained from the Institutional Ethics Committee of My Duc Hospital and informed patient consent was obtained before study enrolment. Results of the study will be submitted for publication in a peer-reviewed journal. TRIAL REGISTRATION NUMBER: NCT03863613 (date of registration: 4 March 2019).